Effect of temperature and Humidity on the Thermal Conductivity [lambda] of Insulation Materials - Kendzierawska, Weronika Anna; Trochonowicz, Maciej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this article is to address the influence of air humidity and testing temperature on the thermal conductivity coefficient ([lambda]) of various thermal insulation materials. This group includes wood-based materials, rock wools, heat-insulating renders, climate boards, and lightweight cellular concretes. These materials are used both indoors and outdoors in buildings.
Keywords: thermal insulation materials; thermal conductivity coefficient; thermal insulation; interior thermal insulation